INTRODUCING HELAEHILI, AN ORAL POETRY FROM SENTANI, PAPUA - Wigati Yektiningtyas Modouw (Celt: A Journal of Culture, English Language Teaching & Literature, 2009)
This paper is partially taken from my research on Sentani oral poetry, helaehili that is sung in mourning occasions or in funerals. It is also usually known as a song of lamentation. The research was conducted in Sentani, Papua for almost 4 years (2004-2008). The data were taken directly from the field through recording. The data were then transcribed, translated into English and analyzed. Through the research, it is found that helaehili is rarely heard. Not many people, especially people who live near Jayapura city and young generation, know the song. It is predicted that helaehili will extinct in some years. The research finds the composition, formula, theme, and notation of helaehili Hopefully, this writing can help and motivate young singers (generation) to learn helaehili.